The Study of Psycho-Social Status of the Elderly People in Rural Area - Udaykiran Bhalge; Bhaskar Gaikwad (Medsci Publications, 2019)
Background: Ageing is a physiological process which is associated with progressive degeneration of all organs and tissues of  the body. Objectives: To study the psychosocial status among elderly male and female people in rural area. Materials and Methods: The present cross sectional study was undertaken in field practice area of Rural Government Medical College to study psychosocial status of Geriatric population. All the elderly (60 years of age and above) were included in present study. Results: Total number of elderly enlisted in study was 442 which are 8.65% of the total population. Out of which number of elderly studied were 393. In the present study 224 (57.00%) were having leisure time activity at home while 169 (43.00%) outside home. Family members of 316 (83.60%) elderly used to honor their advice while family members of 62 (16.40%) elderly used to ignore their advice. 168 (42.75%) were having feeling of loneliness. Conclusions: More number of elderly females had feeling of lone- liness as compared to elderly males. Majority were having sad atti- tude towards life. Loneliness was found to be main reason for sad attitude towards life.